Accidental fortune: natural resources and creation of property regimes in the americas - Arribas Irazola, Guillermo (2017)
Why are some countries of Latin America poor despite their great wealth? From the colony to the republic, many Latin American economies have focused on the extraction of natural resources.In the following article, the author will develop a historical analysis of the Spanish conquest. Specially focusing on the Peruvian case, the author will explain how this background shaped a top-down property regime with longstanding effects.To duly explain the “Accidental Fortune”, a constant comparison will be make between the Spanish conquest of the Americas, and the British colonization of North America. The author will show how the found resources guided each case into different directions.